Beyond the classrooms: the blog as a teaching resource in Linguistics subjects (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
Sometimes, the training program in linguistics is conditioned by a teaching schedule that the professor must follow, that is why it is interesting to use blogs as a way of complementing the education of university students. Thus, this is where the interest of this study lies, because engaging results were found, as it was noted that the contents provided were very well received, having more motivated students, due to the fact that using a blog encouraged their participation in class, allowed them to connect the topics addressed during the course, and, ultimately, helped them to do autonomous work.